2023
DOI: 10.3389/fpsyt.2023.1104664
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits as mediators in the association between SIRT1 rs12415800 polymorphism and depressive symptoms among Chinese college students

Abstract: BackgroundPrevious research has linked polymorphisms in the SIRT1 gene to depressive symptoms, particularly in Chinese individuals. However, it is not clear how personality traits may contribute to this association.MethodsTo explore the potential mediating effect of personality traits, we utilized a mediation model to examine the relationship between the SIRT1 rs12415800 polymorphism and depressive symptoms in 787 Chinese college students. Depressive symptoms were assessed using the Center for Epidemiologic St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…A recent study found a significant link between the SIRT1 rs12415800 polymorphism, a gene associated with longevity, cellular defense against oxidative stress, and depressive symptoms in university students ( 46 ). This association was evident in both codominant ( p = 0.0437) and overdominant ( p = 0.0147) genetic models, demonstrating the heterozygous advantage (similar to our study) of this polymorphism against depressive symptoms ( 47 ).…”
Section: Discussionsupporting
confidence: 87%
“…A recent study found a significant link between the SIRT1 rs12415800 polymorphism, a gene associated with longevity, cellular defense against oxidative stress, and depressive symptoms in university students ( 46 ). This association was evident in both codominant ( p = 0.0437) and overdominant ( p = 0.0147) genetic models, demonstrating the heterozygous advantage (similar to our study) of this polymorphism against depressive symptoms ( 47 ).…”
Section: Discussionsupporting
confidence: 87%